THE EFFECTIVENESS OF HERRINGBONE TECHNIQUE TO ENHANCE STUDENTS’ ABILITY IN COMPREHENDING NARRATIVE TEXT OF THE EIGHTH GRADE STUDENTS AT MTSN TAKENGON II, ACEH TENGAH, ACEH - Cut Dara Ilfa Rahila; Halimatus Sakdiah (INOVISH JOURNAL, 2016)
Abstract: This study was aimed at finding out differences between students who were taught with and without Herringbone technique and the effectiveness of applying the technique to enhance students’ ability in comprehending narrative text Herringbone technique (Deegan, 2006) is a technique that helps students grow their comprehension of the main idea by scheming who, what, when, where, why, and how question on a visual diagram of a fish skeleton. The methodology used in this research was quantitative approach by experimental method. The subjects of this study were 26 students in experimental class and 26 students in control class of MTSN Takengon II, Aceh Tengah, Aceh. In collecting data, the researchers used tests and questionnaire. The data were analyzed by non-parametric statistic, Mc. Nemar test and Chi-square for two independent samples. Result of the data reveals result of Mc. Nemar test by which the Chi-Square observedin experimental classwas higher than Chi Square table and Chi Square obtained in control class (21,05 > 3,814 < 12) and using  Chi-square for two independent samples showed that  the perceived scorewas higher than score of Chi-Square table (4,857>3,814). Moreover, based on the data from questionnaire, the students stated that Herringbone technique was fun to help them understand the materials and the time used was more useful. Hence, the result of Mc. Nemar revealed that there was significant differences between the students taught with and without Herringbone technique and Chi Square for two independent samples proved that Herringbone technique was effective to enhance students’ ability in comprehending narrative test.  Keywords: Effectiveness, Herringbone Technique, Comprehension, Narrative                 Text.